Polycystic ovary syndrome in Salvador, Brazil: a prevalence study in primary healthcare - Gabrielli Ligia; Aquino Estela ML (BMC, 2012)
Abstract Background Polycystic ovary syndrome (PCOS) is a common condition in women of reproductive age. It is characterized by hyperandrogenism, oligomenorrhea/amenorrhea and polycystic ovaries. It is associated with obesity, diabetes, dyslipidemia and cardiovascular disease. No studies have been conducted on the prevalence of PCOS in Brazilian or South American women. Few studies using the Rotterdam criteria have been published. The objective of the present study was to calculate the prevalence of PCOS at primary healthcare level in Salvador, Brazil based on these criteria. Methods This was a cross-sectional, two-phase study conducted in a probability sample of women of 18-45 years of age screened for cervical cancer in the primary healthcare network of the city of Salvador, Brazil. In the first phase, interviews were conducted, weight, height, waist circumference, blood pressure and random blood sugar levels were measured, and the presence of acne and hirsutism was investigated. Women with at least one diagnostic criterion were referred for the second phase, which consisted of specialist consultation, pelvic ultrasonography and hormone measurements for differential diagnosis and/or investigation of a second criterion. Results Of the 859 women interviewed, 88.5% were black and 58.7% had 11 years of schooling or less. A diagnosis of PCOS was excluded in 84.4%, undetermined in 7.1% and confirmed in 8.5% (95%CI: 6.80-10.56). There were no statistically significant differences between these three groups with respect to weight, body mass index, waist circumference, blood sugar levels or arterial blood pressure. Women with PCOS were younger (p = 0.00), taller (p = 0.04), had fewer children (p = 0.00), were better educated (p = 0.01), and had higher total testosterone levels (p = 0.01) and a higher LH/FSH ratio (p = 0.01). Conclusion According to the Rotterdam criteria, the prevalence of PCOS in women seeking primary healthcare in Salvador, Brazil, was 8.5%.